Coherent phonon and charge dynamics in antimony sulfide. - Chong, Wee Kiang. (2013)
Antimony Sulfide (Sb2S3) is a promising light absorbing material due to its small bandgap and large absorption coefficient in the visible region. It has recently gained much research interests as a viable material for semiconductor-sensitized solar cells (SSSCs). While there are numerous studies done to optimize the features of the Sb2S3-SSCs, the phonon and charge dynamics are not thoroughly studied. In this work, transient absorption spectroscopy (TAS) will be used to investigate this.